Quantum mechanics models of the methanol dimer: OH⋯O hydrogen bonds of β-d-glucose moieties from crystallographic data. (18th April 2017) - Cintrón, Michael Santiago; Johnson, Glenn P.; French, Alfred D.
Abstract: The interaction of two methanol molecules, simplified models of carbohydrates and cellulose, was examined using a variety of quantum mechanics (QM) levels of theory. Energy plots for hydrogen bonding distance (H⋯O) and angle (OH⋯O) were constructed. All but two experimental structures were located in stabilized areas on the vacuum phase energy plots. Each of the 399 models was analyzed with Bader's atoms-in-molecules (AIM) theory, which showed a widespread ability by the dimer models to form OH⋯O hydrogen bonds that have bond paths and Bond Critical Points. Continuum solvation calculations suggest that a portion of the energy-stabilized structures could occur in the presence of water. A survey of the Cambridge Structural Database (CSD) for all donor-acceptor interactions in β-D-glucose moieties examined the similarities and differences among the hydroxyl groups and acetal oxygen atoms that participate in hydrogen bonds. Comparable behavior was observed for the O2H, O3H, O4H, and O6H hydroxyls, acting either as acceptors or donors. Ring O atoms showed distinct hydrogen bonding behavior that favored mid-length hydrogen bonds. Graphical abstract: Highlights: Methanol dimer stabilizations were calculated with B3LYP, X3LYP, B3PW91, MP2, B3LYP/SMD methods, and four basis sets. Experimental structures were predominantly found in stabilized energy areas of vacuum phase plots. Atoms-In-Molecules theory showed OH⋯O hydrogen bonds in many arrangements of the methanol dimer. Donor acceptor interactions in β-D-glucose moieties were surveyed using a crystal structure database. β-D-glucose hydroxyls showed similar numbers of donor or acceptor interactions.